Work Induced Stress Among Medical Representatives in Aurangabad City, Maharashtra - Sandip B Patil; Jeewan Meena Singh (Medsci Publications, 2013)
Introduction: As there is a boom in pharmaceutical industry nowadays, the need for the Medical representatives is also increasing simultaneously. The pressure of achieving targets is resulting into the work induced stress among medical representatives. Objective: To assess the work induced stress and various factors responsible for it and also to evaluate some of the health consequences. Method: To achieve the purpose of work, data was collected using a self-administered questionnaire which was distributed to the medical representatives (n=100) by the principal investigator. The survey was carried in the city of Aurangabad during August to October 2012. Data were entered into SPSS (version 17) & analyzed using descriptive statistics. Result: Almost 66% of medical representatives were under pressure & were having some form of stress. Main reasons found were dissatisfaction with job profile (60%) & working hours (63%), continuous pressure for improved performance (73%) and conflicting demands between work & home (78%). Conclusion: There is significant amount of work induced stress among medical representatives. It is creating many health hazards. Unless work induced stress among medical representatives is recognized and reduced they will remain on the brim of getting many health consequences.